Analysis of models of “knowledge-getting” for the expert control system - Вавіленкова A. I. (Problems of Informatization and Control, 2007)
In this article was made overview of models of “knowledge-getting”,analyzed the efficiency of its using while modeling the same situation ,executed analysis of resulting models ,its advantages and disadvantages and finally an optimal model of “knowledge-getting” was defined